EFFECT OF BAGWORM Pteroma pendula Joannis ATTACK ON THE DECREASE IN OIL PALM PRODUCTIVITY - Priwiratama, Hari; Perdana Rozziansha, Tjut Ahmad; Susanto, Agus; Prasetyo, Agus Eko (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
Outbreak of oil palm bagwormPteroma pendula has been reported within the last few years in several plantations in North Sumatra. A study was conductedto determine the impact of P. pendula attacks on oil palm productivity. Aerial photograph was taken in November 2016 andanalyzed to determine the level of damage on each palm canopy. The damage symptoms were classified onto healthy palms ascontrol plants (score 0), mild (score 1), moderate (score 2), severe (score 3), and very severe (score 4). The sample palms wererandomly selected and observed for the sex ratio, bunch number and bunch weight at 18 months after defoliation. The attackof P. pendula at the highest level (score 4) caused a significant effect on sex ratio and the number of bunches produced. Thefresh fruit bunches production was declined 21.02–36.35% on palms with moderate to very severe attack (score 2–4). Similarpalms also have a potential case of inflorescences abortion 18.41–32.54%. However, the average bunch weight was notinfluenced by P. pendula attack.